Systematic review of qualitative studies about malaria in Colombia (2020)
ABSTRACT : Introduction: The research about malaria in Colombia has centered mainly on the biomedical (clinical, parasitological, epidemiological and entomological) field, with little focus on qualitative research. Purpose: Analyzing social categories related to malaria in Colombia, based on qualitative studies published among scientific literature. Methods: Systematic review following Cochrane and PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) recommendations. An ex-ante protocol was applied, comprehensive and reproducible for the search, screening, and extraction of information. Methodological quality was evaluated through SRQR (Standards for Reporting Qualitative Research). Results: 10 studies complied with the protocol; these studies interviewed 500 infected or exposed subjects, program administrators, health professionals, and indigenous people. 40 categories were identified, which account for social-economical, cultural and ecological determiners of malaria; insights and ways to understand the disease at an individual level; malaria consequences, and medical attention, disease control and elimination actions. Conclusion: A wide variety of populations and subjects was considered. They show similar qualitative evidence on structural determiners, family-individual effects, and ways to understand malaria. Motivations to participate in disease interventions are less known, and they constitute the central axis for subsequent studies aimed to improve community engagement in disease control and elimination initiatives.